GOING DIGITAL RUPIAH: SOME CONSIDERATIONS FROM SOVEREIGNTY AND CYBERSECURITY PERSPECTIVES - Zahrashafa Mahardika; Rizky Banyualam Permana; Nadia Maulisa (Bank Indonesia, 2023)
Central banks worldwide are coming to terms with the bits and bytes of digital money, commonly referred to as Central Bank Digital Currency (CBDC). CBDC has been claimed to be safer, more secure, and inherently less volatile, unlike cryptocurrencies, as it is issued and regulated by central banks. The development of digital currency not only emerged in, and isolated developed countries’ monetary policy but also came from the emerging markets. However, the policy and academic discussion on CBDC is clouded as only a significant minority of states have instituted it. From a regulatory point of view, the basic concept of CBDC is still significantly understudied. Among the emerging scholarship, there remains a paucity of study on the (legal) aspects of cybersecurity risk and resilience of the proposed CBDC. This paper explores the role of Bank Indonesia (BI), as the central bank, in implementing CBDC and conducts a preliminary expose associated with cybersecurity risks. This paper shows that CBDC understood as not only usage of Digital Ledger Technologies, (DLTs), but in all models of electronic payment. There are diverging models for the implementation of CBDC, some models involve multiple actors and electronic systems. However, as a currency the Central Bank would ultimately bear the liability for each transaction. Therefore, it is important for BI, as the central bank, consider cybersecurity risks associated with the implementation of CBDC. Cybersecurity risks in the financial sectors including CBDC, is the potential disruption caused by cyber-attacks, IT failures, personnel, and physical or infrastructure security risks.